Determinants of Campylobacter infection and association with growth and enteric inflammation in children under 2 years of age in low-resource settings - Haque, Md Ahshanul (Sci Rep, 2019)
Campylobacter species infections have been associated with malnutrition and intestinal inflammation among children in low-resource settings. However, it remains unclear whether that association is specific to Campylobacter jejuni/coli. The aim of this study was to assess the association between both all Campylobacter species infections and Campylobacter jejuni/coli infections on growth and enteric inflammation in children aged 1–24 months. We analyzed data from 1715 children followed from birth until 24 months of age in the MAL-ED birth cohort study, including detection of Campylobacter species by enzyme immunoassay and Campylobacter jejuni/coli by quantitative PCR in stool samples. Myeloperoxidase (MPO) concentration in stool, used as a quantitative index of enteric inflammation, was measured. The incidence rate per 100 child-months of infections with Campylobacter jejuni/coli and Campylobacter species during 1–24 month follow up were 17.7 and 29.6 respectively. Female sex of child, shorter duration of exclusive breastfeeding, lower maternal age, mother having less than 3 living children, maternal educational level of <6 years, lack of routine treatment of drinking water, and unimproved sanitation were associated with Campylobacter jejuni/coli infection. The cumulative burden of both Campylobacter jejuni/coli infections and Campylobacter species were associated with poor growth and increased intestinal inflammation.